A Discourse on Muslim Women’s Rights in 19th century India: Translated Excerpt from Maulavī Sayyid Mumtāz ‘Alī’s Huqūq un-Nisvāñ (1898) - Abdullah, Sarah; Wasif , Amina (Journal of Research in Humanities, 2024)
The nineteenth century was a time of vigorous social reform in public and private spheres for Indian Muslims. The Muslim household, and especially its female inhabitants became the key ground of contestation in this regard with both assimilative and acculturative movements taking up the issue of women's rights with great zeal. Many texts, including prescriptional novels like Mirat ul-‘Arus and religious treatises like Bahishtī Zewar, were written on women’s duties and responsibilities and soon attained cult status. However, some texts like Maulavī Mumtāz ‘Alī's Huqūq un-Nisvāñ that openly challenged all assumptions regarding women's rights, duties and even traditional exegesis, were precluded from the mainstream narrative. This article includes an extract from a translation of Huqūq un-Nisvāñ that we are presently undertaking. Through this translation, we aim to recover the voice of subversive Muslim reformers like Mumtāz ‘Alī whose discourse has been missing from contemporary understanding of the history of women’s rights in South Asia.